2023
DOI: 10.3390/ijms24108764
|View full text |Cite
|
Sign up to set email alerts
|

Overview on Aneuploidy in Childhood B-Cell Acute Lymphoblastic Leukemia

Abstract: Recent years have brought significant progress in the treatment of B-cell acute lymphoblastic leukemia (ALL). This was influenced by both the improved schemes of conventionally used therapy, as well as the development of new forms of treatment. As a consequence, 5-year survival rates have increased and now exceed 90% in pediatric patients. For this reason, it would seem that everything has already been explored in the context of ALL. However, delving into its pathogenesis at the molecular level shows that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…In this study, 23% of Mexican patients were found to be hypodiploid compared with the ~5% described in other articles discussing hypodiploid ALL. [13][14][15] The increased incidence of hypodiploidy should be further explored to broaden the understanding of leukemia in this patient population, especially considering hypodiploid leukemia has been found to have a specific genomic signature with mutations in Ras and RTK signaling, TP53, RB1, and the IKAROS gene family. In Holmfeldt et al's 16 analysis, 43% of TP53 mutations in pediatric low-hypodipoid ALL were present in nontumor hematopoietic cells suggestive of germline or hematopoietic system-specific involvement compared with all TP53 mutations being of somatic origin in adults.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 23% of Mexican patients were found to be hypodiploid compared with the ~5% described in other articles discussing hypodiploid ALL. [13][14][15] The increased incidence of hypodiploidy should be further explored to broaden the understanding of leukemia in this patient population, especially considering hypodiploid leukemia has been found to have a specific genomic signature with mutations in Ras and RTK signaling, TP53, RB1, and the IKAROS gene family. In Holmfeldt et al's 16 analysis, 43% of TP53 mutations in pediatric low-hypodipoid ALL were present in nontumor hematopoietic cells suggestive of germline or hematopoietic system-specific involvement compared with all TP53 mutations being of somatic origin in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Leukemic cells with hypodiploidy may also undergo endoreduplication resulting in an exact or near-exact doubling of chromosome numbers termed as "masked hypodiploidy" (16,17). Hypodiploidy is divided into three subgroups: near-haploidy with chromosome number 24-30, low hypodiploidy (31-39 chromosomes), and high hypodiploidy (40-45 chromosomes) (13)(14)(15)(18)(19)(20).…”
mentioning
confidence: 99%
“…Only 162 of them have a near-haploid karyotype with chromosome number 24-30 (162/18,999=0.85%) (21). Near-haploid neoplastic B-cells are characterized by commonly loss of chromosomes 3, 7, 9, 15, 16 and 17 and retention of disomies of chromosomes X, Y, 8, 10, 14, 18, and 21 (14,15,20). Somatic genetic alterations targeting receptor tyrosine kinase and RAS signaling, deletion of the IKAROS family zinc finger 3 (IKZF3) gene, and deletions of a histone cluster at chromosome 6p22 have been reported in 70.6%, 13.2%, and 19.1%, of BCP-ALLs with a near haploid karyotype, respectively (13).…”
mentioning
confidence: 99%